2012
DOI: 10.1017/s1368980012000341
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast habits among European adolescents and their association with sociodemographic factors: the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) study

Abstract: Objective: To describe breakfast habits at food group level in European adolescents and to investigate the associations between these habits and sociodemographic factors. Design: Cross-sectional study. Setting: Secondary schools from nine European cities participating in the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Study. Breakfast habits were assessed twice using a computer-based 24 h dietary recall. Adolescents who consumed breakfast on at least one recall day were classified as 'brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 35 publications
8
38
0
1
Order By: Relevance
“…It is likely that children and adolescents who eat breakfast differ from those who do not eat breakfast in ways that also influence educational outcomes. There is a consistent evidence that SES is associated with breakfast eating, with children from higher SES backgrounds more likely to regularly eat breakfast than children from lower SES backgrounds, an effect which is consistent across gender and age (Delva et al, 2006; Moore et al, 2007; Doku et al, 2011; Hallström et al, 2011, 2012; Overby et al, 2011). Similarly, there is well established consistent evidence that SES is a central determinant of academic performance and cognitive ability (Brooks-Gunn and Duncan, 1997; McLoyd, 1998; McCulloch and Joshi, 2001; Machin and Vignoles, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…It is likely that children and adolescents who eat breakfast differ from those who do not eat breakfast in ways that also influence educational outcomes. There is a consistent evidence that SES is associated with breakfast eating, with children from higher SES backgrounds more likely to regularly eat breakfast than children from lower SES backgrounds, an effect which is consistent across gender and age (Delva et al, 2006; Moore et al, 2007; Doku et al, 2011; Hallström et al, 2011, 2012; Overby et al, 2011). Similarly, there is well established consistent evidence that SES is a central determinant of academic performance and cognitive ability (Brooks-Gunn and Duncan, 1997; McLoyd, 1998; McCulloch and Joshi, 2001; Machin and Vignoles, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Because adolescents from families with a low socio-economic status (SES) are more likely to consume a low-quality diet, SES may act as an achievement buffer, thereby partially explaining the relationship between meal pattern, diet and academic achievement [7, 11, 34]. Hence, it is important to account for these variables in cognitive or academic achievement studies, as we have done by adjustment for parental education in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Of these three SES indicators, educational level was found to be the strongest and most consistent in predicting health behaviour [25]. In this study, maternal educational level was used as an indicator of children’s SES because several studies found maternal educational level to be a reliable determinant of children’s dietary behaviour and childhood obesity [9,19,20]. In addition, traditionally, in the majority of the households the mother provides the food for the family and, therefore, maternal educational level also impacts the dietary behaviour of the other members of the family and the home availability of foods.…”
Section: Methodsmentioning
confidence: 99%
“…A literature review found that parental educational level and parental unemployment were unrelated to adolescents and children’s breakfast consumption [18]. However, other studies found a positive association between maternal educational level and children’s breakfast consumption [9,19,20]. Given the inconsistencies in the findings from previous studies and the relative small part of the literature assessing socio-economic disparities in dietary behaviour of children, the first aim of this study is to investigate socio-economic differences in healthy eating behaviours of children (fruit, vegetable and breakfast consumption).…”
Section: Introductionmentioning
confidence: 99%